Analisis Strategi Marketing, Brand Image (Personal Branding) serta Loyalitas terhadap Minuman Starbucks di Kalangan Remaja Milineal - Nurhanifah Nurhanifah; Nazmi Wiki Kartika; Ahmad Husein; Masrona Harahap; Joni Romaito Ritonga; Cindy Indarti Kesuma (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Starbucks is a company that is popular among millennial teenagers, although the prices of food and drinks at the Starbucks company are quite expensive, but for some reason Starbucks remains a hangout place for today's millennial youth elite. Starbucks itself sells hot and cold drinks, coffee beans, salads, hot and cold sandwiches, sweet pastries, snacks and items such as glasses and tumblers. Founded in 1971 in Seattle as a local coffee roaster and retailer, Starbucks expanded rapidly. The Starbucks company that is growing rapidly and is very well known among millennial teenagers is the result of a marketing company itself that is able to promote its products well and can raise the image of its own Starbucks products in the eyes of millennial teenagers so that it becomes a favorite place for tongkorongan hits. Keywords : Marketing, Brand Image, Youth Loyalty To Starbucks Products